(untitled) (Nexo Revista Científica, 2021)
In the present work, an induced draft air cooler was designed to cool an ethanol stream. A sensitivity study was also carried out to evaluate the influence of increasing both the ambient air temperature and the inlet temperature of ethanol on three design parameters. The percentage ratio between the projected area of the fan and the face area of the bay (f) had a value of 43.13%, which is greater than 40%, so it is established that the design carried out is effective. The total pressure drop calculated for the ethanol stream was 3,785.64 Pa, which does not exceed the maximum allowable limit established by the process (10,000 Pa). The calculated power of each driver coupled to the fans reached a value of 897 W. It is suggested to operate at the lowest inlet air temperature possible, and that the feed temperature of the ethanol to the equipment is kept at the value established by the process (80 ºC) so that the parameter f remains above 40%, and the driver power does not increase until reaching high values.